2020
DOI: 10.3389/fpls.2020.513788
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Aquatic Plant Diversity in an Environmentally Sensitive Area, the Lake Taihu Drainage Basin

Abstract: Located downstream of the Yangtze River Delta, the Lake Taihu drainage basin (LTDB) is one of the most developed areas in China. This area currently faces population and development issues, as well as many environmental problems, such as cultural eutrophication, algal blooms, and loss of native aquatic plants. Changes in aquatic biodiversity have received less attention than have changes in terrestrial habitats because relevant observations are lacking. In this study, information from 2010, 2014, and 2018 conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 46 publications
(50 reference statements)
1
6
0
Order By: Relevance
“…A field survey of the distribution of aquatic plants in 2018 revealed that C. caroliniana was a dominant invasive plant in the lower reaches of the Yangtze River (Huang et al, 2020). Prior to our previous investigations, the species was observed to grow well in low sunlight environments, e.g., in areas shaded by bridges, trees and emergent plants where sunlight is partially blocked.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…A field survey of the distribution of aquatic plants in 2018 revealed that C. caroliniana was a dominant invasive plant in the lower reaches of the Yangtze River (Huang et al, 2020). Prior to our previous investigations, the species was observed to grow well in low sunlight environments, e.g., in areas shaded by bridges, trees and emergent plants where sunlight is partially blocked.…”
Section: Introductionmentioning
confidence: 88%
“…The potential invasive ability and consequences of its invasion have often been overlooked in the downstream Yangtze River Basin, despite the high richness of invasive plants found in this area (Feng & Zhu, 2010). A field survey of the distribution of aquatic plants in 2018 revealed that C. caroliniana was a dominant invasive plant in the lower reaches of the Yangtze River (Huang et al, 2020). Prior to our previous investigations, the species was observed to grow well in low sunlight environments, e.g., in areas shaded by bridges, trees and emergent plants where sunlight is partially blocked.…”
Section: Introductionmentioning
confidence: 99%
“…The Lake Taihu Basin is a sensitive area for biological invasion since it is located in one of the developed areas of the Yangtze River Delta in China. A previous study showed that E. crassipes has become the dominant problematic aquatic invasive species in the waters of the Lake Taihu Basin (Huang et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…study showed that E. crassipes has become the dominant problematic aquatic invasive species in the waters of the Lake Taihu Basin(Huang et al, 2020).…”
mentioning
confidence: 99%
“…There are many lakes in the world, and most freshwater lakes experience varying degrees of eutrophication [ 12 , 13 , 14 ]. Detailed information on the distribution of lakes across the world and China is shown in Figure 1 .…”
Section: Introductionmentioning
confidence: 99%